Inside the black box of youth participation and engagement: Development and implementation of an organization‐wide strategy for Orygen, a national youth mental health organization in Australia. Issue 4 (7th September 2020) - Simmons, Magenta B.; Fava, Nicholas; Faliszewski, Jacqui; Browne, Vivienne; Chinnery, Gina; van der El, Kristi; Hodges, Craig; Pennell, Kerryn; Brushe, Mary
Abstract: Aim: The involvement of young people in the development, implementation and evaluation of youth mental health services, policy and research programs is essential to ensure they are appropriate and responsive to the needs of young people. Despite the increasingly central role that youth engagement and participation plays internationally, such activities are rarely described in detail. This article aims to provide a thorough description of the development and implementation of an organization‐wide, 3‐year Youth Engagement and Participation Strategy for Orygen, a national youth mental health organization in Australia. Methods: A descriptive account of the development and implementation of the Strategy, with detailed examples of programs and initiatives. Results: The Strategy was developed based on available evidence, focus groups with key stakeholders and best practice principles. The implementation of the Strategy resulted in a number of programs being delivered that involved a range of young people from across Australia. Despite being successful overall, a number of challenges were experienced. Ongoing considerations include ensuring diversity of partnerships, 'raising the bar' of youth participation and creating meaningful pathways. Conclusions: Youth participation and engagement within a youth mental health context is best seen as an evolving ambition that must remain flexible to the needs of all stakeholders. Despite some challenges and ongoing fine‐tuning, it is possible to successfully implement youth participation and engagement across all areas of youth mental health, including service design and delivery, research and translation, and policy.